2022
DOI: 10.25122/jml-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Sequential (two-step) day 3/day 5 frozen-thawed embryo transfer: does it improve the pregnancy rate of patients suffering recurrent implantation failure?

Abstract: The best time of endometrial receptivity is the missing part of the implantation puzzle in patients with recurrent in vitro fertilization (IVF) failure. There are various treatment plans and strategies to meet the best endometrial timing for implantation. However, the lack of synchronization of the good-quality embryo with the patient's individual “window of implantation” is the hypothesis for most IVF failures so far. Sequential embryo transfer (ET) theoretically extends the availability time of embryos on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…These include a decrease in cumulative live birth rates per couple, an elevated risk of preterm birth, delivering larger-than-average infants for the gestational age, an increased likelihood of monozygotic twins, and a higher incidence of congenital anomalies when compared to embryo transfer during the cleavage stage [ 6 ]. Upon reviewing the literature, there has been research based on sequential embryo transfer in which one day 3 embryo is transferred on day 3 and one blastocyst is transferred on day 5/6 of progesterone in a single menstrual cycle [ 11 , 12 ]. Though initial reports suggested improved pregnancy outcomes using sequential embryo transfer, recent research points out that it has a comparable outcome over blastocyst transfer [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include a decrease in cumulative live birth rates per couple, an elevated risk of preterm birth, delivering larger-than-average infants for the gestational age, an increased likelihood of monozygotic twins, and a higher incidence of congenital anomalies when compared to embryo transfer during the cleavage stage [ 6 ]. Upon reviewing the literature, there has been research based on sequential embryo transfer in which one day 3 embryo is transferred on day 3 and one blastocyst is transferred on day 5/6 of progesterone in a single menstrual cycle [ 11 , 12 ]. Though initial reports suggested improved pregnancy outcomes using sequential embryo transfer, recent research points out that it has a comparable outcome over blastocyst transfer [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, some clinicians have tried to use a sequential ET approach to help patients with RIF increase their chances of pregnancy. Some studies showed that sequential ET did not improve clinical outcomes for patients with RIF (18-20), while other studies suggested that it was more effective toward increasing the clinical pregnancy and live birth rates than day 3 or day 5 ET in these patients (11)(12)(13) randomized trial by Torky et al (13) showed that the implantation and clinical pregnancy rates were significantly higher in patients who underwent sequential embryo transfer than in those who underwent cleavage transfer on day 3 or blastocyst transfer on day 5 in IVF fresh cycles. Arefi et al (11) conducted a prospective study to evaluate the improvement of pregnancy rate in sequential FET on day 3/day 5 in individuals who suffered from RIF and suggested that sequential transfer was more effective than regular day 5.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that sequential ET did not improve clinical outcomes for patients with RIF (18-20), while other studies suggested that it was more effective toward increasing the clinical pregnancy and live birth rates than day 3 or day 5 ET in these patients (11)(12)(13) randomized trial by Torky et al (13) showed that the implantation and clinical pregnancy rates were significantly higher in patients who underwent sequential embryo transfer than in those who underwent cleavage transfer on day 3 or blastocyst transfer on day 5 in IVF fresh cycles. Arefi et al (11) conducted a prospective study to evaluate the improvement of pregnancy rate in sequential FET on day 3/day 5 in individuals who suffered from RIF and suggested that sequential transfer was more effective than regular day 5. A systematic review by Zhang et al demonstrated that the clinical pregnancy rate and live birth rate were higher in the sequential ET group than in the cleavage-stage ET group for women who experienced RIF, and there were no significant differences between sequential ET and blastocyst ET (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation